Peningkatan Kemampuan Berbicara Siswa dengan Menggunakan Teknik Presentation, Practice, Production (PPP) pada Siswa Kelas X SMKN 1 Siborongorong - Gultom, Rut Irmawat (Universitas Tidar, 2025)
This classroom action research aimed to assess the effectiveness of the Presentation, Practice, and Production (PPP) Technique in enhancing students' speaking skills. The participants included 32 students from the tenth-grade TKJ 2 cohort at SMK N 1 Siborongborong. Analysis of the pre-test results conducted during the pre-cycle indicated that the students' proficiency in narrating experiences was inadequate, with a total pre-test score of 1444 and a mean score of 45.12. Only 6.25% of the students achieved the Standard Minimum Achievement (KKM) threshold set at 72. Data were collected through the implementation of the PPP Technique across two carefully planned cycles, each consisting of two instructional sessions. The outcomes of post-test I revealed a significant improvement in the students' speaking abilities, with a total score of 1596 and a mean of 49.87. In post-test I, 12.5% of the participants reached the KKM. Results from cycle II indicated further progress, with a total score for post-test II of 2276 and a mean score of 71.12. In post-test II, 65.62% of the students achieved the KKM, indicating that the intervention was successful in advancing their speaking skills. Additionally, this research illustrated a positive transformation in learning behavior, attributed to the favorable responses elicited by the techniques employed. In summary, this action study establishes that the PPP Techniques significantly contributed to improving the speaking abilities of tenth-grade students at SMK N 1 Siborongborong, and it is anticipated that these findings will motivate educators in their efforts to teach speaking, particularly in vocational school contexts.